Nilai Spiritualitas dalam Praktik Literasi Al-Qur’an Siswa: Studi Kasus di SMAN 6 Kabupaten Tangerang - Santani Santani; Asep Muhyidin (Universitas Mathla'ul Anwar Banten, 2026)
The phenomenon of declining spiritual awareness among adolescents has become a serious challenge in modern education. Schools are expected not only to produce intellectually intelligent generations but also students with strong spiritual character. This study aims to examine the spiritual values internalized through Qur’anic literacy practices among students at SMAN 6 Tangerang Regency and to explore how these values shape students’ religious and moral character.This research employed a qualitative approach with a case study method. Data were collected through participatory observation, in-depth interviews with Islamic Education (PAI) teachers and students, as well as documentation of Qur’anic literacy activities. The data were analyzed using data reduction, display, and verification techniques.The results indicate that Qur’anic literacy practices at SMAN 6 Tangerang Regency are implemented through three main activities: morning tadarus (recitation), tahsin–tahfidz (reading and memorization), and thematic tadabbur (Qur’anic reflection). Through these activities, five dominant spiritual values were found to be internalized among students: (1) sincerity, (2) discipline, (3) gratitude and inner peace, (4) responsibility, and (5) social empathy. These values are developed through habituation, teacher role-modeling, and shared spiritual experiences within the school environment.The findings reinforce Bandura’s Social Learning Theory and Zohar & Marshall’s concept of Spiritual Intelligence, suggesting that spiritual values can be transmitted through continuous social interaction and reflective religious practices. The study concludes that Qur’anic literacy practices serve as an effective medium for fostering students’ spirituality in public schools, as they enhance not only religious literacy but also form a spiritual habitus that encourages positive behavior and emotional balance.